Concrete Incorporated With Silica Fume And Manufactured Sand Under Acidic Nature (JOURNAL OF ADVANCES IN CHEMISTRY, 2016)
Now a dayAcid attack is growing threat to concrete structures. Using some alternate materials as partial replacement of cement and sand in the concrete is an important factor that enhances the performance of concrete in an aggressive environment. In this present study, the cement is replaced with silica fume by 10 % and the sand is replaced with manufactured sand up to 50%. The selection of these replacement materials involves a balance between economy and durability.The specimens are immersed in 2% concentration of both acids such as sulphuric acid and hydro chloric acid at 28 days. The grade of concrete is M30. From the results, it is observed that the concrete containing 10% silica fume and 40% manufactured sand has the better performance in acid environment.Â Â